Propagação e estabelecimento de plantas de pequizeiro - Levi Fraga Pajehu (2018)
There is still little information on the establishment of C. brasiliense, after planting in the field, as well as strategies that should be adopted to ensure its survival, especially from the point of view of water requirements. Therefore, the present work had the objective of evaluating irrigated and non - irrigated propagation methods regarding the emergence, growth and physiology of pequi trees in the initial stage of establishment. The study was carried out in a randomized block design in subdivide plots. The plots consisted of the presence and absence of irrigation, while the sowing of pyrenes constituted the subplots: recently dispersed, recently dispersed treated with GA3, stored for 30 days in shed and stored treated with GA3, and planting of seedlings. The emergence and survival of plants, vegetative development, through stem diameter, plant height, number of leaves and leaf area were evaluated. In addition, rates of assimilated carbon, stomatal conductance, transpiration, and water use efficiency were obtained. Data were submitted to ANOVA, the means compared by the Tukey test at the 5% level of significance. In the irrigated plots, the treatment stored with GA3 presented emergence of seedlings superior to three months of planting. After 16 months of planting, seedling emergence stabilized, with increments in the newly dispersed treatment without GA3, from 2.5% to 21.8%, while treatments stored with and without GA3 reached 28.6% and 31%, respectively. In the plots without irrigation, seedling emergence did not reach 6%. Freshly dispersed pyrenes with GA3 allowed greater survival of seedlings, but in irrigated seedlings survival rate was low, about less than 50% and did not differ from the non-irrigated seedlings. Regardless of the use of irrigation, the increase in the growth rate of the seedlings was superior to the seedlings from the pyrenes, except for those stored in GA3. Concerning to the physiological aspects, the higher rate of assimilated carbon, stomatal conductance and greater efficiency in water use were observed in irrigated plants. Although the transpiration was not affected by irrigation, it showed a reduction in July. Irrigation influenced the physiological aspects and the emergence of seedlings, as well as pregerminative treatments; the planting of seedlings and stored pyrenes treated with GA3 is a more indicated alternative in the planting of pequi tree.